2020
DOI: 10.1002/cac2.12096
|View full text |Cite
|
Sign up to set email alerts
|

The ongoing trends of patient‐derived xenograft models in oncology

Abstract: The ongoing trends of patient-derived xenograft models in oncology 1 MAIN TEXT Patient-derived xenograft (PDX) models have garnered increasing attention since the last decade. These models are typically characterized by the implantation of fresh patient-derived tumor tissues into immunodeficient mice. PDX models are well recognized in academic laboratories, pharmaceutical institutions, and specialized commercial organizations as having the ability to recapitulate genomics, transcriptomics, proteomics, and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…This is similarly reflected in the results of Oberg et al, who explored the use of linear mixed‐effects models with complex correlation structures in the context of ovarian cancer PDX studies 20 . Additional work has examined the need for unified frameworks of PDX studies and their evaluation to better ensure replicability and optimal use of study data 5,21,22 …”
Section: Discussionmentioning
confidence: 95%
“…This is similarly reflected in the results of Oberg et al, who explored the use of linear mixed‐effects models with complex correlation structures in the context of ovarian cancer PDX studies 20 . Additional work has examined the need for unified frameworks of PDX studies and their evaluation to better ensure replicability and optimal use of study data 5,21,22 …”
Section: Discussionmentioning
confidence: 95%
“…The PDX models have highly similar histopathological and genetic characteristics to the maternal tumors. Studies have shown that, the drug sensitivity of the PDX model to anticancer drugs is highly correlated with the clinical treatment outcomes of cancer patients [11]. PDX models are still the most used models in the pharmaceutical industry and personalized medicine in the past few decades although they are time-consuming and cost-ineffective [12][13][14].…”
Section: Biotechnology In Cancer Researchmentioning
confidence: 99%